Effectiveness of Leadership Tungku Tigo Sajarangan in The Development of Nagari Nyiur Lambai Pelangai - Rika Aniska; Tati Murni; Nurhizrah Gistituati (Bisma The Journal of Counseling, 2022)
The purpose of this study was to determine the effectiveness of the leadership of Tigo Jarangan in the development of Nagari Nyiur Melambai Pelangai, Ranah Pesisir District, Pesisir Selatan Regency. This study uses a descriptive method with a qualitative approach and uses an informant sampling technique. For data collection used observation or observation methods, documentation and interviews. So the results and discussion of this study indicate the implementation of leadership from the ulama, cadiak clever and penghulu in building the nagari together and working together for the future of the younger generation and the nation. The background of the problem in this study is the lack of coordination between formal leaders and traditional leaders, namely the ulama, outskirts of intelligence and the penghulu, the lack of loyalty or cooperation between the tigo sajarangan furnace and the formal leaders, the lack of roles from the ulama, cadiak clever and penghulu to build a nagari from a physical point of view and provide direction.